Blended Learning in Higher Education for Informatics Engineering Education: A Bibliometric and Systematic Literature Review - Renny Permata Saputri; Nizwardi Jalinus; Rijal Abdullah; Ridwan; Monica Fransisca (bit-Tech, 2025)
The evolution of digital technology has prompted a significant transformation in higher education, particularly within the Informatics Engineering curriculum. In this landscape, blended learning has surfaced as a vital strategic method, combining traditional face-to-face teaching with online learning to boost flexibility, effectiveness, and student engagement. This research utilizes a Systematic Literature Review (SLR) and bibliometric analysis to map the trends and research focus of blended learning. Data was gathered from Google Scholar for publications from 2021 onward, using specific keywords. An initial pool of 1,850 articles was refined through a PRISMA-based screening process, resulting in 33 highly relevant articles for detailed analysis. The findings show that publication activity was highest in 2021, with major contributions from the United Kingdom, Indonesia, and the United States. Key themes identified in the literature include the use of Learning Management Systems (LMS), the flipped classroom model, and project-based learning. The evidence consistently suggests that blended learning improves educational outcomes, increases student motivation, and fosters essential 21st-century skills. However, challenges such as insufficient infrastructure and the need for enhanced educator competency remain. This paper recommends strengthening institutional policies and providing faculty training to support the successful and sustainable implementation of blended learning, especially in technology and vocational education.